2019
DOI: 10.14569/ijacsa.2019.0100721
|View full text |Cite
|
Sign up to set email alerts
|

New Approach of Automatic Modulation Classification based on in Phase-Quadrature Diagram Combined with Artificial Neural Network

Abstract: Automatic Modulation Classification (AMC) with intelligent system is an attracting area of research due to the development of SDR (Software Defined Radio). This paper proposes a new algorithm based on a combination of k-means clustering and Artificial Neural Network (ANN). We use constellation diagram I-Q (In phase, Quadrature) as basic information. K-means algorithm is used to normalize data transmitted and pollute by the Additive White Gaussian Noise (AWGN), then the new diagram obtained is considered as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…We choose four modulations (BPSK, 8 PSK, 4 QAM, 32 QAM), which are frequently used in several studies. As presented in the table, our method shows an improvement in terms of recognizing different modulations used at low SNRs, particularly at 4 dB 53 …”
Section: Simulation Results and Discussionmentioning
confidence: 80%
“…We choose four modulations (BPSK, 8 PSK, 4 QAM, 32 QAM), which are frequently used in several studies. As presented in the table, our method shows an improvement in terms of recognizing different modulations used at low SNRs, particularly at 4 dB 53 …”
Section: Simulation Results and Discussionmentioning
confidence: 80%
“…To compare our results with those which exist in the literature, we will do it with four modulations because it is these modulations that several authors have used [3][4][5]14]. But the comparison with other results of the literature is difficult as was mentioned in papers [7,13] because there are no standard databases of modulations that everyone should use to facilitate comparison and the parameters of experiments differ from one author to another.…”
Section: Comparisons With Other Resultsmentioning
confidence: 99%
“…In [3] and [4] have demonstrated that the application of a clustering algorithm (fuzzy c-means, k-means, k-center) to normalize data polluted by Gaussian noise only cannot be used to recognize the modulation used. It will be necessary to couple given results to a Neural Network to fulfill the task of classification [3,14]. Our proposed algorithm is a supervised learning case where all modulations are known by receiver and recognition is done through the use of the I-Q constellation diagram which will be considered as a pixel-coded picture.…”
Section: Coding Of the Constellation Diagrammentioning
confidence: 99%
See 1 more Smart Citation